La música tradicional del pueblo Kichwa de Pastaza en el fortalecimiento de la memoria social-cultural de los estudiantes de primer año de bachillerato de la unidad educativa intercultural bilingüe “Amauta Ñampi” de la ciudad de Puyo. Año lectivo 2018-2019 - Yasacama Andi, Marlon Ricardo (2020)
The general objective of this research is to establish the impact of the traditional music of the Kichwa people of Pastaza on the strengthening of the social-cultural memory of the first-year high school students of the "Amauta Ñampi" Intercultural Bilingual Educational Unit, in order to know and value the traditional Amazonian Kichwa music. To this end, different communities in the province of Pastaza have been visited in search of elders, since they are people full of knowledge about the culture and even more so about its music. The universe investigated for the purpose of optimizing the time of the investigation and in pursuit of fulfilling the objectives set, it has been considered appropriate to seek out elders from different communities in the province of Pastaza to know their music and select a repertoire with songs that have lived in the orality of the same, for this purpose as a research technique was applied an interview. Also to determine the degree of knowledge that the students have about the traditional music kichwa amazon, a survey was applied to later carry out the obtaining of data, determining a total population of 51 people, the methods that were used to be able to carry out this investigation with effectiveness have been; the scientific method and the ethnographic method. After the results obtained, once the respective tabulation was made, the results reflect that the students have no knowledge about the traditional Amazonian kichwa music; this is due to the fact that they do not have a direct contact with this music, that is why it is suggested the realization of a recital of traditional Amazonian kichwa music, where they can directly appreciate this traditional music rhythm in order to strengthen and enrich the culture of the kichwa people of Pastaza.